Breaking through barriers to Norwegian fresh salmon trade with China by a new production technology - Luan, Lan (Universitetet i Tromsø, 2011)
Atlantic salmon export plays an important role in the total Norwegian seafood export. EU countries are currently the main markets for Norwegian salmon export. China is one of the countries which are expected to have an increased demand for Norwegian salmon. Norwegian fresh salmon exporters are currently facing the trade barriers with respect to new inspection regime and high transportation costs when they export fresh salmon to China. This study is investigating whether Coolnova salmon, fresh frozen salmon using proton magnetic freezing technology, may break the trade barriers of Norwegian fresh salmon export to Mainland China. Firstly is the meaning of preferred fresh quality of Norwegian Atlantic salmon and secondly is the potential market value of the Coolnova salmon for the wholesalers and the supermarket in Hong Kong estimated. A sample of fresh chilled, Coolnova and frozen salmon fillets were tested by wholesalers and supermarket managers who gave their quality judgement recorded in a questionnaire. Different perceptions and attitudes were expressed related to both quality factors like fatness and colour influenced by the different fish feeding, sizes and fillet cuts of the tested salmon samples as well as factors related to the application of novel freezing and thawing technologies where Coolnova salmon has its advantage. The results show that freshness is a preferred product attribute of salmon characterized by appearance as a distinctive orange colour, clear white oil lines and a hard texture and smooth and juicy taste. The results indicate that Coolnova salmon after fresh-frozen and thawed, may satisfy the markets requirements for freshness and furthermore gain a cost advantage by the opportunity to move distribution from an expensive fresh airfreight to a low cost frozen sea freight. Frozen salmon can be kept in freezers for a long time without quality degradation and would thereby not be affected by the new quality inspection regime which hampers the fresh fish import to China. Coolnova salmon can ...